Response growth and yield of red onion (Allium ascalonicum L.) of Bima variety using cholchine and cow manure - Foarota, Florus; Saragih, Wismaroh Sanniwati; Br Jabat, Yelfi Yana Linda (Universitas Islam Malang, 2024)
Demand for onions is always increasing but is constrained by large areas, expensive fertilizer, sensitivity to climate change, expensive seed prices, pests, and disease attacks. The size of local shallot bulbs is much smaller than imported shallots, but the color of the bulbs is redder and the taste is spicier. In order to overcome this problem, there needs to be an effort to improve the plant and shallot cultivation activities using colchicine to obtain superior properties and in combination with cow manure. . This research aims to determine the effect of colchicine and cow manure on the growth and production of the Bima variety of shallots. The research was carried out in January–September 2023 in the experimental garden of the Faculty of Agriculture, Universitas Pembinaan Masyarakat Indonesia, Medan. The research method used a completely randomized design, namely colchicine concentration (0 ppm, 300 ppm, and 600 ppm), soaking time (0; 4 hours; 8 hours), and cow manure (0; 2kg; 4 kg), which was repeated in 3 repetitions. The results showed that the concentration of colchicine, soaking time, and cow manure had a significant effect on plant height, number of leaves, number of tillers, tuber diameter, wet tuber weight per hill, and wet tuber weight per plot. The 300 ppm soaking concentration treatment had a significant effect on these factors. for 8 hours and 4 kg of cow manure, and all treatments were significantly different from control plants.